2020
DOI: 10.11648/j.jdmp.20200604.15
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation and Antimicrobial Activity of Six Plants Used in Children’s Ailments Treatment in Niger

Abstract: Resistance phenomena of infectious agents to synthesis drugs and the high cost of these drugs led to medicinal plants as an alternative against infectious disease. The objective of this study is to characterize different classes of secondary metabolites and to test the antibacterial activity of six plants: Bauhinia rufescens Lam, Blepharis linariifolia PERS, Chrozophora brocchiana Vis, Gardenia ternifolia Schum and Thonn, Indigofera astragalina DC, Phyllanthus pentandrus Schumach &Thonn, used in traditional me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The aqueous extract was tested on S. typhimirium of the isolated strains (Mahamane et al, 2020) [13] . Nasereldeen et al, in 2018 [14] showed the hepatoprotective properties of the hydroethanolic extract obtained from the whole plant.…”
Section: Limeum Pterocarpum (L)mentioning
confidence: 99%
See 4 more Smart Citations
“…The aqueous extract was tested on S. typhimirium of the isolated strains (Mahamane et al, 2020) [13] . Nasereldeen et al, in 2018 [14] showed the hepatoprotective properties of the hydroethanolic extract obtained from the whole plant.…”
Section: Limeum Pterocarpum (L)mentioning
confidence: 99%
“…The hexane extract of the plant seeds did not show activity against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Aspergillus niger (Osama et al, 2017) [18] . [18] (Mahamane et al, 2020) [13] Hydroethanolic [5] . It is used in the composition of several recipes used in the treatment of infectious diseases.…”
Section: Limeum Pterocarpum (L)mentioning
confidence: 99%
See 3 more Smart Citations